Effect of Fintech Adoption on MSME Financial Performance in West Tulang Bawang Barat - Tiara Prama Nur’Aizah; M.Ridwan Siddik; Dias Alief; Eka Travilta Oktaria (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the effect of fintech usage on the financial performance of Micro, Small, And Medium Enterprises (MSMEs) in Tulang Bawang Barat Regency. Research Methodology: This study employs a quantitative approach using a survey method. Data were collected from MSME owners using structured questionnaires. A purposive sampling technique was applied, resulting in 50 respondents being selected. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. Results: The results show that the use of fintech has a positive and significant effect on MSME financial performance. Fintech adoption improves transaction efficiency, financial record management, and access to financial services, thereby enhancing the overall business performance. Conclusions: This study concludes that fintech usage significantly improves the financial performance by enhancing transaction efficiency, financial management, and access to financial services. However, the effectiveness of fintech adoption depends on the readiness and capability of MSME actors to utilize digital financial technology. Limitations: This study is limited to MSMEs in Tulang Bawang Barat Regency and considers only the fintech usage as the independent variable. Therefore, these findings may not be generalizable to other regions. Contributions: This study contributes to the literature by providing empirical evidence of the impact of fintech on MSME financial performance at the regional level. Practically, the findings offer insights for MSME owners and policymakers to promote Fintch adoption as a strategy to improve financial performance.